2020
DOI: 10.1038/s41598-020-59752-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing pattern of subpleural alveolar ducts

Abstract: in this study we have utilized an optical clearing method to allow visualization of a heretofore undescribed subpleural acinar structural organization in the mammalian lung. the clearing method enables visualization of the lung structure deep below the visceral pleura in intact inflated lungs. In addition to confirming previous observations that the immediate subpleural alveoli are uniform in appearance, we document for the first time that the subpleural lung parenchyma is much more uniformly organized than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…In agreement with a previous report demonstrating that type 2 alveolar epithelial cells (AT2s) are the major source of GM-CSF 32 , 33 , we confirmed that Csf2 gene expression is detected in AT2 cells using previously published dataset 34 (Extended Data 5c). Consistent with these observations, we found that CD301b + cDC2s reside in the interstitium around alveolar ducts that are surrounded by alveoli 35 ( Fig. 4g ).…”
Section: Resultssupporting
confidence: 87%
“…In agreement with a previous report demonstrating that type 2 alveolar epithelial cells (AT2s) are the major source of GM-CSF 32 , 33 , we confirmed that Csf2 gene expression is detected in AT2 cells using previously published dataset 34 (Extended Data 5c). Consistent with these observations, we found that CD301b + cDC2s reside in the interstitium around alveolar ducts that are surrounded by alveoli 35 ( Fig. 4g ).…”
Section: Resultssupporting
confidence: 87%
“…at expiration (Fig. 5 b) that are about twice as larger as reported in prior work that analyzes 2D images of fixed inflated lungs (about 40 m) 36 , 37 . Furthermore, in this study, the maximum value of the alveolar diameters is > 120 m, which is three times larger than the reports.…”
Section: Resultsmentioning
confidence: 53%
“…In this study, synchrotron x-ray imaging directly lets us compare alveolar morphology between live and fixed lungs. Specifically, the alveolar morphology has been reported as polyhedral 5 7 with 40 ~ 58 μm diameter in fully inflated fixed lungs 20 22 . However, we reveal that alveolar morphology in live lungs shows spherical and 2 ~ 3 times the larger alveolar diameter (81.6 ± 18.2 μm) even at the expiration than reported in fixed lungs.…”
Section: Discussionmentioning
confidence: 99%